Representações do município de Rio Claro - SP: uma leitura da cartografia infantil - Costa, Christiane Fernanda da [UNESP] (2015)
Until the 70s of the XX century the cartographic community defined the true cartographic representations as those created with scientific rigor, considering maps only those based on technical and scientific knowledge. However, from the aforementioned decade, the geographer and cartography historian, John Brian Harley (1932/1991), encouraged an epistemological change by defending the recognition of any kind of cartographic representation as a form of language expressed by different civilizations. This way, the Çatal Höyük map, found in the center-western of Turkey, Eurasia, elaborated at approximately 8200 years ago, is now considered one of the oldest cartographic representations. In this sense, the purpose of this study focused on investigating the representations of the locality produced by students of the 3rd year of a public elementary school in the municipality of Rio Claro, São Paulo, Brazil. Several activities were promoted during gatherings, planned and carried out in the first semester of 2014, with 58 students from 8 to 9 years old. In the methodological perspective of observation of evidence, a discussion related to the teaching of Scholar Geography and Cartography was elaborated within the process of education and literacy. As a result, different productions of texts and mental maps were obtained, in which was observed that the students properly used the elements of urban space of the municipality of Rio Claro, once they studied this space under different perspectives and languages, all within the context of geographical teaching and learning. Thus, by means of the records, the representations of the locality integrated into the teaching of different languages were analyzed. With this research we hope to contribute to the discussion of the teaching of Geography and Scholar Cartography in the context of basic education